The Bochum Survey of the Southern Galactic Disk: II. Follow‐up measurements and multi‐filter photometry for 1323 square degrees monitored in 2010 – 2015. Issue 6 (July 2015) - Hackstein, M.; Fein, Ch.; Haas, M.; Ramolla, M.; Pozo Nuñez, F.; Barr Domínguez, A.; Kaderhandt, L.; Thomsch, K.; Niedworok, N.; Westhues, Ch.; Chini, R.
Abstract This paper is the second in a series describing the southern Galactic Disk Survey (GDS) performed at the Univer‐sitätssternwarte Bochum near Cerro Armazones in Chile. Haas et al. (2012, Paper I) presented the survey design and the characteristics of the observations and data. They identified ∼2200 variable stars in an area of 50 square degrees with more than 50 observations in 2011. Here we present the first complete version of the GDS covering all 268 fields with 1323 square degrees along the Galactic disk including revised data from Paper I. The individual fields were observed up to 272 times and comprise a maximum time span between September 2010 and May 2015. We detect a total of 64 151 variable sources, which are presented in a catalog including some of their properties and their light curves. A comparison with the International Variable Star Index (VSX) and All Sky Automated Survey (ASAS) indicates that 56794 of these sources are previously unknown variables. Furthermore, we present U, B, V, r ′, i ′, z ′ photometry for all sources within the GDS, resulting in a new multi‐color catalog of nearly 16×106 sources detected in at least one filter. Both the GDS and the near‐infrared VISTA Variables in the Via Lactea survey (VVV) complement each other in the overlap area of about 300 square degrees enabling future comparison studies. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)